A mirror without reflection: The Purple Spot in Brazilian theater criticism (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
In this article, we discuss the different metaphors used by the critical reception of the work The purple spot, by Plínio Marcos, when looking for its meaning in Brazil at the end of the 20th century, approaching the main keys of reading the text and the spectacle in the view of some of the main critics Brazilian theatricals active at the time of their staging. In the work, the author resumes the theme of life behind bars from the conflicts of a group of prisoners, also opting, this time, for the approach to AIDS. For that, we start from the discussion of Susan Sontag, in order to understand the more general scope of the problem raised by her reflection, by the criticism of the play and the show.
Keywords: The purple spot; Modern Brazilian Theater; Theatrical criticism; Aids; Plínio Marcos